The Effects of Instagram Use on Body Image, Body Satisfaction and Ways of Losing Weight – A Quantitative Study - Toktam Namayandeh, Joorabchi; Mokhtar, Jafari (KOME, 2024)
The present study investigates the direct effect of Instagram use on various ways of losing weight, examines the mediation effects of body satisfaction and body image, and the moderator effects of gender and marital status. A total of 520 people who both used Instagram and undertook body surgery participated in the study and filled in the online and printed versions of our questionnaire. Partial least squares regression was used to test the research hypotheses and the relationships among the variables. The results revealed that body image mediated the effect of the purpose of Instagram use on ways of losing weight; however, no mediation effect of body image and body satisfaction was found for patterns and purposes of Instagram use apart from exercise. The relationship between the purposes and pattern of Instagram usage on body satisfaction was significant. However, patterns of Instagram use had no impact on body image, while this relationship for purpose was significant. The implications of the study are discussed.